Peer Effects on Violence : Experimental Evidence from El Salvador - Dinarte Diaz, Lelys (World Bank, Washington, DC, 2020)
This paper provides experimental evidence of the effect of having peers with different propensities for violence in the context of an afterschool program. By randomly assigning students to participate in the program with a set of similar or diverse peers in terms of violence, the study measures the effects of segregation or integration on students' behavioral, neurophysiological, and academic outcomes. The paper also exploits a discontinuity around the median of the propensity for violence distribution, to measure the impacts of segregation on marginal students. The results indicate that integrating students with different propensities for violence is better for highly and less violent children than segregating them. In particular, the intervention can have unintended effects on misbehavior and stress, if highly violent students are segregated and treated separately from their less violent peers.